Blending Biodiesel in Fishing Boat Fuels for Improved Fuel Characteristics - Lin, Cherng-Yuan (Frontiers in Energy Research, 2014)
Biodiesel is a renewable, clean, alternative energy source with advantages, such as excellent lubricity, superior biodegradability, and high combustion efficiency. Biodiesel is considered for mixing with fishing boat fuels to adjust their fuel characteristics so that toxic pollutants and greenhouse-effect gas emissions from such shipping might be reduced. The effects of blending fishing boat fuels A and B with various weight proportions of biodiesel are experimentally investigated in this study. The results show that biodiesel blending can significantly improve the inferior fuel properties of both fishing boat fuels and particularly fuel B. The flash points of both of these fuels increases significantly with the addition of biodiesel and thus enhances the safety of transporting and storing these blended fuels. The flash point of fishing boat fuel B even increases by 16% if 25 wt.% biodiesel is blended. The blending of biodiesel with no sulfur content is found to be one of the most effective ways to reduce the high sulfur content of fishing boat fuel, resulting in a reduction in the emission of sulfur oxides. The addition of only 25 wt.% biodiesel decreased the sulfur content of the fishing boat fuel by 37%. The high kinematic viscosity of fishing boat fuel B was also observed to be reduced by 63% with the blending of just 25 wt.% biodiesel. However, biodiesel blending caused a slight decrease in heating value around 1–4.5%.